The electrifying stomach - Koch, K. L. (Neurogastroenterology and motility, 2011)
The stomach is electrified and subject to eurhythmic and dysrhythmic electrical events – much like the heart. The normal human slow wave ranges from 2.5 to 3.75 cycles per min (cpm), tachygastrias range from 3.75 cpm to 10.0 cpm and bradygastrias from .5 to 2.5 cpm, the gastric dysrhythmias of men and women. In this issue of Neurogastroenterology & Motility, O’Grady, et al. describe the gastric dysrhythmias of pigs in electrocardiology terms. Printed circuit boards (PCB) with multi‐electrode arrays (160–192 electrodes) were attached to the stomach serosa. Gastric dysrhythmias occurred in eight of the 16 anesthetized pigs and were analysed by manually and by computer. The patterns of dysrhythmias were reminiscent of cardiac dysrhythmias: conduction blocks, ectopic foci, re‐entrant wave fronts, premature and aberrant slow waves and regular and irregular tachygastrias. The authors suggest gastric dysrhythmias recorded in pigs may be relevant to human gastric dysrhythmias and electricity‐based therapies. The categories of porcine gastric dysrhythmias may help to understand the spectrum of gastric dysrhythmias of men and women recorded over the past 25 years. Analogies between gastric and cardiac neuromuscular disorders are explored because Neurogastroenterology is evolving as a clinical and therapeutic field utilizing knowledge of gastric rhythmicity and electro‐contractile events. Interstitial cells of Cajal are the pacemaker cells of the stomach and loss of cells or faulty circuitry appear to be key pathways to gastric dysrhythmias. Gastric electrophysiology (EP) labs, human and animal, are needed to test hypotheses and advance understanding of human gastric dysrhythmias and upper GI symptoms.